Spatial and temporal variations in creep rate along the El Pilar fault at the Caribbean‐South American plate boundary (Venezuela), from InSAR. Issue 11 (14th November 2016) - Pousse Beltran, Léa; Pathier, Erwan; Jouanne, François; Vassallo, Riccardo; Reinoza, Carlos; Audemard, Franck; Doin, Marie Pierre; Volat, Matthieu
Abstract: In eastern Venezuela, the Caribbean‐South American plate boundary follows the El Pilar fault system. Previous studies based on three GPS campaigns (2003–2005–2013) demonstrated that the El Pilar fault accommodates the whole relative displacement between the two tectonic plates (20 mm/yr) and proposed that 50–60% of the slip is aseismic. In order to quantify the possible variations of the aseismic creep in time and space, we conducted an interferometric synthetic aperture radar (InSAR) time series analysis, using the (NSBAS) New Small BAseline Subset method, on 18 images from the Advanced Land Observing Satellite (ALOS‐1) satellite spanning the 2007–2011 period. During this 3.5 year period, InSAR observations show that aseismic slip decreases eastward along the fault: the creep rate of the western segment reaches 25.3 ± 9.4 mm/yr on average, compared to 13.4 ± 6.9 mm/yr on average for the eastern segment. This is interpreted, through slip distribution models, as being related to coupled and uncoupled areas between the surface and ~ 20 km in depth. InSAR observations also show significant temporal creep rate variations (accelerations) during the considered time span along the western segment. The transient behavior of the creep is not consistent with typical postseismic afterslip following the 1997 Ms 6.8 earthquake. The creep is thus interpreted as persistent aseismic slip during an interseismic period, which has a pulse‐ or transient‐like behavior. Key Points: New observations of aseismic slip along a segment of a major plate boundary (El Pilar fault, Venezuela) Evidence of spatial and temporal variations in creep over the 2007–2011 period Creep occurs on the segment ruptured in 1997, it corresponds to an afterslip which evolved into interseimic creep showing transients